Contraceptive self-injection through routine service delivery: Health worker perspectives from Uganda - Morozoff, Chloe; Cover, Jane; Namagembe, Allen; Nsangi, Damalie; Komunyena Tumusiime, Justine; Stout, Auroras; Kidwell Drake, Jennifer (Frontiers in Global Women's Health, 2022)
Self-care reproductive health innovations are increasingly valued as practices that enable women to manage their fertility with greater autonomy. While self-care, by definition, takes place beyond the clinic walls, many self-care practices nonetheless require initial or follow up visits to a health worker. Access to self-care hinges on the extent to which health care workers who serve as gatekeepers find the innovation appropriate and practical. Self-injection of subcutaneous depot medroxyprogesterone acetate (DMPA-SC) is being introduced and scaled in many countries. In late 2018, health workers in Uganda began offering self-injection of DMPA-SC in the public sector, and this study examines health workers’ views on the acceptability and feasibility of training women to self-inject. We conducted in-person interviews with 120 health workers active in the self-injection program to better understand provider practices, program satisfaction, and their views on feasibility. A subset of 77 health workers participated in in-depth interviews. Quantitative data was analyzed using Stata (v14) software, and chi square and student t tests used to measure between group differences. Qualitative data was analyzed using Atlas.ti, employing an iterative coding process, to identify key themes that resonated. The majority of health workers were very satisfied with the self-injection program and reported it was moderately easy to integrate self-injection training into routine service delivery. They identified lack of time to train clients in the clinic setting, lack of materials among community health workers, and client fear of self-injection as key challenges. Community health workers were less likely to report time challenges and indicated higher levels of satisfaction and greater ease in offering self-injection services. The relatively high acceptability of the self-injection program among health workers is promising; however, strategies to overcome feasibility challenges, such as workload constraints that limit the ability to offer self-injection training, are needed to expand service delivery to more women interested in this new self-care innovation. As self-injection programs are introduced and scaled across settings, there is a need for evidence regarding how self-care innovations can be designed and implemented in ways that are practical for health workers, while optimizing women’s successful adoption and use.